The horror of corporate harms: purdue pharma and the opioid epidemic - Crofts, Penny (Crime, law and social change, 2024)
There has been a great deal written about Purdue and the opioid epidemic in multiple disciplines, including dismay about the failure of the criminal legal system to adequately conceptualize and respond to Purdue’s responsibility for causing the epidemic. Rather than lingering on the failure of the criminal legal system, we read Purdue’s responsibility as and through horror. The harms caused by Purdue do not fit into criminal legal categories as they are currently written and, instead, are more analogous to harms portrayed in the horror genre. Moreover, Purdue could achieve these harms only through the failure and betrayal of people and institutions of authority, a classic trope of the horror genre. We develop a concept of routine horror to explore the ways in which corporate harms are inflicted through everyday practices and products, enabled by routine systems of regulations and laws. On this account, the routines enable the harms and are harmful in and of themselves, leaving us with no one to trust and no place to turn. In the absence of effective law, we remain stuck in a horror story.